1996
DOI: 10.1073/pnas.93.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Principles of protein-protein interactions.

Abstract: This review examines protein complexes in the Brookhaven Protein Databank to gain a better understanding of the principles governing the interactions involved in protein-protein recognition. The factors that influence the formation ofprotein-protein complexes are explored in four different types of proteinprotein complexes-homodimeric proteins, heterodimeric proteins, enzymeinhibitor complexes, and antibody-protein complexes. The comparison between the complexes highlights differences that reflect their biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

92
1,935
5
8

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,520 publications
(2,040 citation statements)
references
References 48 publications
92
1,935
5
8
Order By: Relevance
“…Consistent with this notion, the stability of the early intermediate and the rate of stable complex assembly have a strong dependence on ionic strength (32). Critical roles of electrostatic interactions in enhancing protein interaction kinetics have been predicted theoretically (33,34) and demonstrated in multiple cases (35)(36)(37)(38); our results further emphasize the role of such interactions in stabilizing assembly intermediates, which provides an effective way to accelerate the overall assembly process.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with this notion, the stability of the early intermediate and the rate of stable complex assembly have a strong dependence on ionic strength (32). Critical roles of electrostatic interactions in enhancing protein interaction kinetics have been predicted theoretically (33,34) and demonstrated in multiple cases (35)(36)(37)(38); our results further emphasize the role of such interactions in stabilizing assembly intermediates, which provides an effective way to accelerate the overall assembly process.…”
Section: Discussionsupporting
confidence: 71%
“…Comparison between epitopes and other types of proteinprotein interfaces in transient hetero-complexes with respect to physico-chemical and structural characteristics (Bogan and Thorn, 1998;Jones and Thornton, 1995, 1996, 1997aNeuvirth et al, 2004), revealed general similarities between the two types of protein regions. Namely, preference for tyrosine and tryptophan residue and unorganized secondary structures was found to characterize both types of interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of antibody-antigen co-crystal data remained limited, these analyses revealed general principles of protein-protein interactions, which also had implications for antibody-antigen interactions. Jones and Thornton (1995, 1996, 1997a compared interfaces and non-interface regions with respect to physico-chemical and structural properties at the amino acid level, such as ASA, amino acid composition, degree of protrusion, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…uk/bsm/PP/server/index.html) (Jones and Thornton 1996), is 1159 Ã… 2 . How does this value compare to that of a typical crystal contact interface?…”
Section: Analysis Of the Crystal Packing Of Thioredoxin Mmentioning
confidence: 99%